Medical emergency preparedness in Nepalese dentistry: an analysis of existing practices - Kumar Yadav, Anil; Kumari Yadav, Poonam; Thakur, Amresh; Kumar Mahato, Vivek (Journal of Chitwan Medical College, 2025)
Introduction: Medical emergencies in a dental clinic can be alarming to any clinician, but these situations become relatively less alarming with adequate precautions and necessary training. Effective management of emergencies reduce potential complications which requires a dental clinic set up with dentists and team member well prepared with training, essential medicine and equipment. The present study aimed to assess the status of preparedness of dental clinics of Nepal for medical emergencies. Method: A descriptive cross-sectional study was conducted from 30 Apr 2023 to 29 Apr 2024 after ethical clearance. Dentists registered in Nepal Medical Council and Nepal Dental Association were selected using simple random sampling method. Dentists not actively practicing were excluded. An online google form of pre-tested structured close ended self-administered questionnaire was used for data collection. The descriptive statistics frequency and percentage was analysed using Statistical Package for Social Science version 29. Result: In the study of 622 dentists, syncope 491(78.9%) and hypoglycaemia 357(57.5%) were the most common medical emergencies. Most of the medical emergencies occurred during extraction of tooth 402(64.7%) and local anaesthesia administration 363(58.4%). Only 235(37.8%) of the dental clinics have emergency medical kit in their clinics. Only half 329(52.9%) have Basic Life Support training and almost all 603(96.8%) agreed there should be training for dentist on medical emergency preparedness. Conclusion: The preparedness of dental clinics for medical emergencies were sub-standard and inadequate. The clinics lacked the basic needed emergency kit whereas the dentists and team lacked in emergency management team and preparedness.